Towards personalised, gamified systems: An investigation into game design, personality and player typologies - Ferro, L.; Walz, Steffen; Greuter, S. (2013)
With the rise of Gamification, the boundaries between play and games on the one hand, and everyday life on the other are being challenged, and as a result game play is entering the realm of everyday life. We believe that with the breakdown of this dichotomy and with the increasing presence of game elements in everyday life in the form of Gamification, there are more factors such as users intrinsic motivation, agenda, learning preferences and personality that should be considered in the design of gamified systems. In this paper, we investigate the relationship between player types, and personality types and traits. By way of investigating pre-existing player type models as well as personality traits and types models, we have identified possible relationships between these two areas of research, and in that, between the realm of games, and the realm of the everyday. As a result, we propose a table identifying these possible relationships between player types, personality types and traits, and game elements and game mechanics and discuss how this connection may impact the design of gamified systems and offer insight towards more user orientated design objectives.